2014
DOI: 10.1136/jnnp-2013-306787
|View full text |Cite
|
Sign up to set email alerts
|

Impulse control disorder in patients with Parkinson's disease under dopamine agonist therapy: a multicentre study

Abstract: ICD was significantly associated with the use of the non-ergolinic oral DA (pramipexole and ropinirole) when compared with transdermal non-ergolinic DA (rotigotine). Since pramipexole, ropinirole and rotigotine are non-ergolinic DAs with very similar pharmacodynamic profiles, it is likely that other factors including route of administration (transdermal vs oral) explain the difference in risk of ICD development.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
191
6
9

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 218 publications
(221 citation statements)
references
References 34 publications
15
191
6
9
Order By: Relevance
“…Recent studies suggest ICDs occur in upwards of 40% of PD patients [2], with males more likely to report multiple impulsive behaviours than females [3]. While there are currently no reliable predictive markers for the development of an ICD, patients with higher traits of impulsivity may be more susceptible, although this is yet to be established.…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies suggest ICDs occur in upwards of 40% of PD patients [2], with males more likely to report multiple impulsive behaviours than females [3]. While there are currently no reliable predictive markers for the development of an ICD, patients with higher traits of impulsivity may be more susceptible, although this is yet to be established.…”
Section: Introductionmentioning
confidence: 99%
“…Although rotigotine has been reported to confer a lower risk compared with other DAs (Garcia‐Ruiz et al., 2014; Moore, Khalaj, et al., 2014; Rizos et al., 2016), rotigotine has D3 receptor affinity, and furthermore, in a post hoc analysis of six open‐label extension studies, 71 of 786 patients (9%) with rotigotine treatment developed ICB (Antonini et al., 2016). Hence, rotigotine could be a risk factor for the development of ICB.…”
Section: Discussionmentioning
confidence: 99%
“…Two impulse control disorders were encountered in the current study, as it has been reported previously in small numbers of patients. A recent study was seen that ICD was significantly associated with the use of the nonergolinic oral DA (pramipexole and ropinirole) when compared with transdermal non-ergolinic DA (rotigotine) [4] [14] [18] [19].…”
Section: Discussionmentioning
confidence: 99%